Deep travel : in Thoreau's wake on the Concord and Merrimack - Leff, David K. (American land and life series., 2009)
In the hot summer of 2004, David Leff floated away from the routine of daily life just as Henry David Thoreau and his brother had done in their own small boat in 1839. Fortified with Thoreau's observations as revealed in A Week on the Concord and Merrimack Rivers, Leff brought his own concept of mindful deep travel to these same New England waterways. His first-person narrative uses his ecological way of looking, of going deep rather than far, to show that our outward journeys are inseparable from our inward ones.